Investigation of Targeted Process Control for Adjusting the Macrostructure of Freeze Foams Using In Situ Computed Tomography - Johanna Maier; Vinzenz Geske; David Werner; Thomas Behnisch; Matthias Ahlhelm; Tassilo Moritz; Alexander Michaelis; Maik Gude (Ceramics, 2022)
Freeze foams are novel and innovative cellular structures that are based on a direct foaming process and that can be manufactured using any material that can be processed by powder technology. The foam formation process is characterized by the highly complex interaction of various process and material parameters that were chosen empirically and that have so far been difficult to reproduce. To allow properties to be specifically tailored towards certain applications, it is necessary to examine the phenomena observed during foam formation as well as the impact of the process and material parameters on the structural constitution to deduce guidelines for manufacturing and quality assessment (e.g., mechanical strength, cell and pore sizes, pore size distribution). The variety of possible applications are a result of the wide spectrum of initial suspensions and especially the foam structure properties derived from process parameters such as the cell geometry, pore size distribution, fraction of open and closed porosity, and the textures of the cell struts. Due to earlier findings, the focus of this paper focuses on adjusting and tailoring the macrostructure (homogenization of the pore sizes and their distribution inside foam cells) to create load- and application-adapted ceramic foams. To this end, an experiment was designed using previously identified pore and characteristic influencers (air and water content, temperature of the suspension, pressure reduction rate) as influencing parameters. Their interconnected impacts on selected target values were examined during the freeze foaming process using an in situ freeze foaming device inside an X-ray.